2018
DOI: 10.1136/neurintsurg-2018-013803
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the global outflow angle on recanalization after endovascular treatment of middle cerebral artery bifurcation aneurysms

Abstract: This study emphasizes that a new parameter, the global outflow angle, can be predictive of recanalization for MCA bifurcation aneurysms treated by EVT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…Similar observations regarding the effect of parent artery lumen are also made by Usmani et al 53 using 3D contour plots of six different time instants. In their paper De La Torre et al 54 reported the outflow angle as one of the risk factors for recananlization in cerebral aneurysms. We find it re-affirming that presented tools in this work are also able to capture the effect of change in outflow angle, due to different downstream vasculature in both geometries, on foam based treatment, see Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…Similar observations regarding the effect of parent artery lumen are also made by Usmani et al 53 using 3D contour plots of six different time instants. In their paper De La Torre et al 54 reported the outflow angle as one of the risk factors for recananlization in cerebral aneurysms. We find it re-affirming that presented tools in this work are also able to capture the effect of change in outflow angle, due to different downstream vasculature in both geometries, on foam based treatment, see Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…The inflow angle (IA) was composed of the A2 segment and the axis of the aneurysm (Figure 1A), 22 and the GOA was composed of the A2 segment and the bilateral A3 segments (Figure 1B). 21 The A2 diameter (A2D) near the neck, and the A3 diameter (A3D) of the pericallosal artery and the callosomarginal artery, near the neck were calculated. The difference in diameter between the A2D and A3D (A2-3D), and the difference in diameter between the bilateral A3Ds (A3-3D) were also calculated.…”
Section: Methodsmentioning
confidence: 99%
“…20 Global outflow angle (GOA) was reported as a predictor of re-treatment in coil embolization for unruptured middle cerebral artery bifurcation aneurysms. 21 In the present study, we investigated the treatment outcomes and predictors of silent ischemic events in coil embolization for unruptured DACA aneurysms, focusing on morphological characteristics, especially the angle between the aneurysms and the surrounding blood vessels, and their association with silent ischemic events.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Além dos locais clássicos identificados anteriormente, outras características dos aneurismas de ACM podem ser avaliadas para prever a formação dessas lesões e os resultados após o TE ou cirúrgico. Entre eles, podemos citar o lado, tamanho, multilobulação, relação domo/colo, relação colo/vaso principal, relação tamanho do aneurisma/ diâmetro do vaso principal, incorporação por ramos lenticuloestriados ou ramos distais da ACM e angulação da bifurcação principal(17,20,(44)(45)(46)(47)(48)(49).Como discutido anteriormente no tópico "hemorragia subaracnóidea", o aumento dos ângulos de bifurcação pode produzir alterações com aumento do estresse hemodinâmico além da tensão protetora das bandas de fibras de colágeno densamente compactadas, consequentemente, causando um remodelamento destrutivo na parede dos vasos e ocasionando a formação de aneurismas. Foi observado também que o ângulo de bifurcação apresenta uma relação inversa com o diâmetro do segmento M1.…”
unclassified